Seeking support through solidarity: female leader’s experiences of workplace solidarity in male-dominated professions - Pillay-Naidoo, Daphne; Vermeulen, Corlette (Frontiers in Psychology, 2023)
While there is a plethora of research that documents the numerous barriers affecting female leaders in the modern workplace, there is a lack of literature which focuses on strategies or motivating resources that women use to navigate the workplace environment. Despite facing significant barriers in their leadership journeys, there are female leaders who are able to overcome these barriers to achieve leadership positions. These women leaders draw on personal and external motivating factors to assist them in dealing with the challenges associated with being a female leader as a result, research on motivating strategies for women’s career progression is a research topic that warrants immediate attention. Female solidarity as a motivating resource has been gaining traction in the field of leadership studies and can be seen as a supportive resource that can be used by current and aspiring female leaders to progress in underrepresented environments. Female solidarity in the workplace is identified as the mutual agreement, support and collective responsibility of interests experienced amongst women in the workplace that will be displayed in instances where women are required to indicate actions for collectiveness and undivided support. Although female solidarity is but only one of the many strategies that can be implemented to motivate females in leadership positions, the increase of female solidarity in the workplace is expected to alleviate the conditions that reinforce essentialist notions of the “queen bee syndrome” in which women are seen as unsupportive of each other. Understanding the experiences of female solidarity in the workplace will assist in exposing wider systematic inequalities especially in male dominated work environments. A qualitative research approach was used for this study, following an interpretive descriptive design. A total of 14 semi-structured interviews were conducted with female leaders in male-dominated professions within South Africa. Results of the study were analysed in line with three primary content areas i.e., barriers to female solidarity in the workplace, benefits of female solidarity in the workplace and workplace interventions to increase solidarity.